2009
DOI: 10.1080/17290376.2009.9724926
|View full text |Cite
|
Sign up to set email alerts
|

Challenges impacting on the quality of care to persons living with HIV/AIDS and other terminal illnesses with reference to Kanye community home-based care programme

Abstract: HIV/AIDS has been found to be a challenging disease to humanity, its challenge spin-offs falling especially on to the caregivers of those infected and affected by the virus. This paper aims to discuss the challenges influencing the state of caregiving in the Kanye community home-based care (CHBC) programme in Botswana. The study was qualitative in design and explorative in nature, involving 82 primary caregivers in focus group discussions, and 5 CHBC nurses in individual interviews. Caregivers were found chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 2 publications
(1 reference statement)
0
23
0
Order By: Relevance
“…1,7,22 In Botswana, 1 it was found that elderly caregivers did not use the care package they were provided with because they felt that using gloves would imply that they do not love the person in their care. In contrast, caregivers in a Namibian study 7 expressed anger at the risk they were exposed to.…”
Section: Discussionmentioning
confidence: 99%
“…1,7,22 In Botswana, 1 it was found that elderly caregivers did not use the care package they were provided with because they felt that using gloves would imply that they do not love the person in their care. In contrast, caregivers in a Namibian study 7 expressed anger at the risk they were exposed to.…”
Section: Discussionmentioning
confidence: 99%
“…This perception that lack of food affects quality of care is supported by studies showing that opportunistic infections are more common in people with gross nutritional depletion and malnutrition (DoH, 2001;World Food Programme, 2006). Indeed, a 1999 survey by the non-governmental organisation (NGO), Hope Worldwide, found that lack of food was the most urgent need affecting the caregiving process (Kang'ethe, 2009). Furthermore, other areas of care are also affected.…”
Section: Effects Of Poverty On Quality Chbc: Food Securitymentioning
confidence: 99%
“…The poor living conditions of many clients have a major impact on the ability of volunteer caregivers to provide quality care(Kang'ethe, 2009). The DoH's Policy on Quality in Health Care for South Africa…”
mentioning
confidence: 99%
“…Unarguably, poverty is a social evil and a form of deprivation that can either be relative or absolute (Kang'ethe, 2009). Absolute poverty is a form of deprivation whereby the subsistence is actually below the minimum requirements for physical well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Absolute poverty is a form of deprivation whereby the subsistence is actually below the minimum requirements for physical well-being. Although the index for absolute poverty may be debated about, it is usually based on a quantitative scale and in a broader sense it is taken to include issues such as income as well as goods and services (Hulme, Moore & Shepherd 2001;Kang'ethe, 2009). On the other hand, relative poverty entails a circumstance or experience in which the income or consumption level is below the prevailing or surrounding location where they reside or a fraction of the national country average (Hulme, Moore & Shepherd, 2001).…”
Section: Introductionmentioning
confidence: 99%